Words : britannica discovery library - Hartman, Carrie (Encyclopaedia Britannica, Inc. Chicago, 2005)
This book delves into the intricate evolution of language, highlighting the significance of words in shaping human communication. It examines the origins, variations, and cultural implications of vocabulary across different societies.